Dynamic Calculation of a Multi-Storey Building under Longitudinal-Shear Vibrations (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Within the framework of the bimoment theory of thick plates, a spatial dynamic continuum model of multi-storey buildings under longitudinal seismic impact is proposed. Formulas are proposed for determining the reduced moduli of elasticity and density. The natural frequency, displacement and stress values of a multi-story building were calculated.